Ksiądz Franciszek Bażyński - społecznik, wydawca, patriota (1801-1876) - Biesiada, Jacek (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
Fr. Franciszek Bażyński was born in Poznań in 1801. After receiving the holy orders in 1824 in Wrocław he was a curate at the St. Adalbert's church in Poznań and then a parish priest in Ceradz Kościelny, Niepruszewo and Lwówek. In the latter two places he founded two temperance societies and reading rooms for the general public. For contacts with emissaries of the Polish Democratic Society (Towarzystwo Demokratyczne Polskie) he was imprisoned in Berlin and Magdeburg in the years 1836-1840. In 1848 and in the years 1850-1851 he was a deputy to the Prussian parliament. In 1849 Archbishop Leon Przyłuski appointed him the parish priest of the St. Adalbert's church in Poznań. In 1863 he founded Wydawnictwo Dobrych i Tanich Książek (the Publishing House of Good and Cheap Books), which was closed down by the Prussian authorities in 1873. During the ten years of its activity it released nearly 40 book titles for the general public on religious and historical themes as well as literary fiction. The overall issue amounted to 140 000 copies. To mark the 50th anniversary of his priesthood his friends published a commemorative book titled Warta (The Sentinel). Fr. F. Bażyński died in 1876, and the coffin with his body was interred in the vaults of the St. Adalbert's church in Poznan, where it remains until today.